An Exploratory Study on the Emotional Climate within Family Firms: The Impact of Emotional Dissonance - Vandekerkhof, Pieter; Hoekx, Laura; Claus, Brent (European Journal of Family Business, 2022)
This study focuses on the emotional climate of family firms. In particular, we highlight the expression of emotions by emphasizing the phenomenon of emotional dissonance within these firms. Emotional dissonance, a person-role conflict, originates from the discrepancy between expressed and experienced emotions. Additionally, we look into the role of the (non)family status of the CEO and the generational phase of the firm in the occurrence of the emotional climate. Research on emotions within firms has steadily increased over the years, although almost always neglecting family firms. This is a remarkable observation given the preeminence of family firms in the worldwide economy and the overlap between business and family these firms are confronted with. Through an in-depth qualitative study, we unravel both the impact of family firms’ emotional climate and the facets that contribute to this climate.